Designing a proposed electronic counseling program based on some Web 2.0 applications to Reducing family stress of Parents of children with intellectual disabilities - Alswat, Shrog Aidh; Ashhry, Ali Mohammad Alkalthamy (Journal of Educational and Psychological Sciences, 2023)
The current research was aimed at designing a proposed electronic indicative program based on some Web2.0 applications. It is intended for parents who have children with intellectual disabilities to help them alleviate the pressure they are experiencing. Moreover, the experimental single-set design has been adopted and the research sample consisted of (30) targets 15 were mothers 15 were fathers. In order to verify the effectiveness of the proposed program a psychomotor (Alsartawi & Ashakhs, 1998). Indeed, the results emerged difference statistically at (0.05) between the grades of the experimental group members in tribal and post measurements on the scale of psychological pressures for the good of the post measurement. The researcher recommended to recruit the Web 2.0 applications more widely in various programs and training courses and recommended that attention should be paid to providing mentoring programs with different objectives and purposes for families with disabilities children in an electronic format that serves their cognitive needs and takes into account their different circumstances.
Keywords: Counseling program; Web 2.0 applications; social media; Intellectual disabilities; psychological stress